Categorisation of dairy production systems: A strategy for targeting meaningful development of the systems in Uganda - Mubiru, S.L.; Tenywa, J.S.; Halberg, N.; Romney, Dannie L.; Nanyeenya, W.; Baltenweck, Isabelle; Staal, Steven J. (2007)
Dairy production is a major contributor towards national economies and household food security and incomes in sub-Saharan Africa (SSA). Milk production in the region is estimated at 1.27 million metric tonnes year-1. However, this level of milk production is inadequate for the existing human population who would require 103 million metric tonnes year-1. In Uganda, milk production only meets approximately 20% of the population's nutritional requirements. As such, methods need to be sought to increase milk production in the region. Research efforts have made strides in identifying the causes of the production-demand gap in the SSA region and a spectrum of interventions to bolster the productivity. Unfortunately, these efforts have by far yielded insignificant results. First and foremost, for exploiting the full potential of the dairy cattle population in the region, among the critical elements often overlooked in research and development processes is the recognition of systematic parametric variations within the sector, which if considered could provide entry-points for targeting intervention efforts. One such high potential entry-point is the recognition of the existence of a dairy intensification "vector" across a country or region, along which exist sections with sequentially marked nuclei of fairly uniform socio-economic and biophysical dairy sub-systems features. To enhance the process of targeting research and development in the Ugandan dairy sector, dairy production systems in the country were categorised on basis of level of intensification of production. Data were collected from 300 households in Mbarara, Masaka and Jinja districts in Uganda. The major variables derived from the data for the categorisation process were those related with milk production, expenditure, income, land area and cattle herds. The data was subjected to a cluster analysis which although produced 16 groups only five had prominent membership (above 5% of the farms). The five major clusters were selected as representative of the dairy production systems. A ranking system was used to develop an intensification continuum for the 5 systems. Herding-on own and communal land (cluster 9) was the least intensive, this was followed by Herding-mainly on own land (cluster 12) and Fenced (cluster 8) respectively. Semi-Zero Grazing (cluster 15) and Zero Grazing (cluster 13) were the most intensive dairy production systems with the latter being at the highest end of the continuum.